Analisis Korelasi Kondisi Keluarga Siswa di Kelas X (Studi Kasus MAUWH Tambakberas Jombang) - Wardani, Dian Kusuma; Mufarrohah, Laily (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2022)
Parent is the closest people to their children and who have the most influence on their children's education. There are five factors that influence the roles of parents, include of parents educational background, parents types of work, parents economic level, available time and the number of family members. This research conducted by quantitative which use a correlation analysis approach and aims to determine the relationship between students family condition variables X class MAUWH Tambakberas Jombang. The data collection in this study use a questionnaire by taken 60 students in X class from three class which are MIPA 2, IIS 2 and AGAMA 2 as the respondents. Based on the results of the study, the results of the validity test and reliability test for the questionnaire were valid and reliable. For the correlation test between variables, it is known that all the variables has a correlation and the significant can be proven by the value of r count > r table. It was concluded that the factors of parents' educational background, type of parent's occupation, parents' economic level, available time and number of family members were the family conditions that influenced the role of the parents students X class MAUWH Jombang.